BUSINESS PROCESSES OF TERRITORIES’ ATTRACTIVENESS FORMATION - SYHYDA, Liubov; MALYTSKYI, Ivan; MALII, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Today’s globalized world challenges territories – cities, regions, and countries – to increase competitiveness and attractiveness. Territories compete for resources, investments, tourists, and new residents, striving to stand out. Territories achieve it by creating a unique brand based on real competitive advantages, which helps to consolidate a positive image of the territories. In this regard, scientific approaches to studying the attractiveness of regions as a business process with clearly defined stages and tools are becoming increasingly important, which is the purpose of this article. The article examines the attractiveness of a territory as a complex socio-economic phenomenon that can be considered in the format of a business process. Also, the article analyses the existing approaches to interpreting the concept of «attractiveness of a territory». It distinguishes it from the related concept of «competitiveness of a territory2 by two criteria - key elements and time limits. The business process of forming the attractiveness of a territory is developed. It includes six stages - strategic planning, SWOT analysis, stakeholder survey, best practices study, and competitive advantages identification. The article considers different approaches to quantitative assessment of the attractiveness of a territory based on a set of indicators combined with other components, which comprehensively characterize various aspects of attractiveness. It is determined that indicators are used to measure efficiency, openness, identity, strategy, services, infrastructure, culture, innovation, and other aspects of the territory. Such approaches as ‘magnetism and profitability’ and the Global Attractiveness Index (GAI) are taken into account. The results obtained can be used to develop strategies for developing cities and regions and for comparative analysis of territorial potential.